2020
DOI: 10.1371/journal.pntd.0008668
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme immunoassays for detection and quantification of venoms of Sri Lankan snakes: Application in the clinical setting

Abstract: Background Detection and quantification of snake venom in envenomed patients' blood is important for identifying the species responsible for the bite, determining administration of antivenom, confirming whether sufficient antivenom has been given, detecting recurrence of envenoming, and in forensic investigation. Currently, snake venom detection is not available in clinical practice in Sri Lanka. This study describes the development of enzyme immunoassays (EIA) to differentiate and quantify venoms of Russell's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The major issue with snakebite diagnosis is the cross-reactivity among venoms, as some proteins in each venom overlap and detection devices are rarely species-specific, instead detecting a range of species when using immunological techniques (24). To date, most diagnostic antibodies exhibit poor specificity (12)(13)(14)(15), thus hindering the correct selection and dosage of antiserum. We showed here that the principles of venom similarities and the underlying cross-reactivities of the same genus could be applied to develop universal genus-specific diagnosis tools for snakebite (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major issue with snakebite diagnosis is the cross-reactivity among venoms, as some proteins in each venom overlap and detection devices are rarely species-specific, instead detecting a range of species when using immunological techniques (24). To date, most diagnostic antibodies exhibit poor specificity (12)(13)(14)(15), thus hindering the correct selection and dosage of antiserum. We showed here that the principles of venom similarities and the underlying cross-reactivities of the same genus could be applied to develop universal genus-specific diagnosis tools for snakebite (11).…”
Section: Discussionmentioning
confidence: 99%
“…The application of specific antibodies in the diagnosis of snakebite can accurately judge the type of snakebite and prevent unwarranted and wasteful administration of antivenom ( 11 ). To date, most of the diagnostic antibodies were polyclonal antibodies with poor specificity and often saturate at a high concentration of snake venom, for example, the polyclonal diagnostic antibodies for distinguishing hematotoxin and neurotoxin and the polyclonal diagnostic antibodies for individual snake species ( 12 ), while the contents of snake venom in the plasma of different patients, bitten by snakes of the same species, vary up to 100-folds (from a few nanograms to hundreds of nanograms) ( 12 , 13 ). Although monoclonal antibodies have been reported, they cannot be used in the clinic because of their low specificity ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the universal presence of this protein in both elapid and viper venoms raise questions on its utility as a marker for species-specific venom identification. Polyclonal antibody-based enzymatic-or radioactivity-assays can detect venom up to 1-5 ng/mL in the sample [28,44]. These assays PLOS NEGLECTED TROPICAL DISEASES require long detection time and expertise which is undesirable for rapid point-of-care testing of envenomation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, diagnosis for snake envenomation relied primarily on visual examination followed by polyclonal sera-based detection strategies such as, immunodiffusion, immunofluorescence, hemagglutination, immunoelectrophoresis, radioimmunoassay; which in turn were limited by their tendency to crossreact with the closely related venoms, the reduced assay sensitivity, poor scalability for industrial production, and a prolonged-time of detection [21][22][23]. With advancing technologies, portable ELISA based kits, optical immunoassay, dot-blot assay, and family-specific protein identification tests were developed for detection of the specific venom using a three-step affinity-purified polyclonal antibody [24][25][26][27][28]. Affinity-purified polyclonal antibody raised against a cocktail of selective venoms is limited by its scalability for industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a venom quantification study was able to demonstrated venom antigen in circulation up to 24 h post bite in human due to scarcity of specific antivenom for Hypnale spp. envenoming 20 .…”
Section: Introductionmentioning
confidence: 99%